Study of a water‐soluble fluorescent sensor based on the Eu(III) pefloxacin complex. (5th August 2016) - Wen, Chaohao; Yang, Jinglian; Zeng, Zhi; Gao, Jinwei; Zheng, Yuhui
Abstract: The antibiotic type organic structure pefloxacin binds well with europium (III) ions as a useful scaffold for assembling optical probes and allows energy transfer from ligand to metal ions through coordination linkages. This water‐soluble chemosensor demonstrated significant 'off–on (red)' changes from an alkaline to a neutral environment (pH 14–8). The emission changed from red to blue under acidic conditions (pH 7–2). The whole process was completely reversible and effective within the pH range 2 to 14. Moreover, this probe system exhibited distinct luminescence quenching upon the addition of Cu 2+ or Fe 3 + . This general modular route will permit easy detection and the concept can be extended to a variety of quinolones for sensing purposes.